A Profile of Working Memory Ability in Poor Readers - Dawes, Emily; Leitao, Suze; Claessen, Mary; Nayton, M. (2015)
Objective: This study aimed to provide a comprehensive working memory profile of a group of children with established poor reading ability. Methods: Participants included a group of established “poor readers” and a group of age- and gender-matched controls with typically developing reading ability. The participants completed a comprehensive battery of assessments examining four components of working memory—the central executive, phonological loop, visuospatial sketchpad, and episodic buffer. Results: As predicted, the poor reading group scored significantly lower than the typically developing reading group on measures of the phonological loop and central executive. There were no significant differences between the two groups on measures of the visuospatial sketchpad or episodic buffer. Contrary to predictions, a subgroup of poor readers with poor visuospatial working memory was not found, further highlighting the inconsistent findings in this area of working memory. Conclusions: The results provide support for past research findings of deficits in the phonological loop and central executive of poor readers. The finding of typical episodic buffer functioning demonstrates the potential to draw on this relative strength in implementing interventions with poor readers. This implicates the importance of increasing awareness of specific working memory deficits in poor readers, and may guide future research into more effective teaching strategies and interventions for this population.